Enriching Medical Student Learning Experiences. (January 2020) - Kallail, K James; Shaw, Pam; Hughes, Tyler; Berardo, Benito
Objective: Medical students should develop skills in assessing their own learning needs and developing strategies to meet those needs. Medical curricula should be designed to provide active and enriching ways to explore medicine beyond the classroom. The program should enrich the elements of motivation, discovery, innovation, social services, cultural exploration, and personal development. The University of Kansas School of Medicine instituted a new curriculum in 2017 called ACE (A ctive, C ompetency-based, andE xcellence-driven). Eight 1-week courses of enrichment experiences are embedded within the first 2 years of the curriculum. Methods: After each of 8 medical content blocks, students are required to participate in a 1-week, nongraded enrichment experience according to their own learning needs and interests. Students choose the type of enrichment activities including clinical experiences, professional development, leadership development, research and scholarly activity, and community engagement. Students select their top enrichment choices and a computer lottery makes the assignments from their designations. Students engaged in research and scholarly activity are guided to appropriate research mentors. Results: A total of 196 enrichment activities at 3 campuses were developed for 211 students during the first 2 years of medical school. Most students selected clinical experiences with enrichments available in most medical specialties and subspecialties. Students also use enrichment weeks to conduct research/scholarly activity, particularly those students pursuing the Honors Track. A total of 2071 enrichment experiences were completed in the first 2 years. Conclusions: Most enrichments involved clinical experiences, although research/scholarly activity and professional development enrichments also were popular. Evaluations from students and antidotal data suggested enrichments are popular among students and a good change of pace from the usual rigorous activities of the curriculum. Because of the large number of experiences required to conduct the enrichment weeks, a continuous process of evaluation is required to maintain the program. Therefore, flexibility is required to administer the program.